Strengthening Educational Quality through a PPEPP-Based Internal Quality Assurance System at MI Al Jihad - Siti Rizqina Fitriani Mutmainnah; Mulyawan Safwandy Nugraha (MANAZHIM, 2026)
Educational quality assurance in Islamic elementary schools requires the PPEPP cycle to function not merely as an administrative procedure but as a sustainable mechanism for institutional improvement. This study aims to analyze the implementation of the PPEPP-based Internal Quality Assurance System at MI Al Jihad, focusing on internal quality audits, follow-up actions, and the strengthening of quality culture. A qualitative case study design was employed, with data collected through in-depth interviews, observations, and documentation involving the madrasah principal, quality assurance team, and teachers. The data were analyzed thematically through data condensation, data display, and conclusion drawing. The findings indicate that MI Al Jihad conducts internal quality audits through semester-based supervision and annual Teacher Performance Assessments. Audit findings are followed up through individual guidance, collective meetings, teacher coaching, workshops, continuous professional development, and online training. Nevertheless, the implementation remains suboptimal because follow-up actions require more rigorous monitoring, clearer performance indicators, and more systematic documentation. A quality culture has begun to develop through discipline, exemplary leadership, and professional responsibility; however, quality awareness has not been internalized consistently among all teachers. The study concludes that the effectiveness of the PPEPP cycle depends on the madrasah’s capacity to translate audit findings into measurable improvement actions and a collectively sustained quality culture. These findings contribute to educational quality management by proposing an integrative framework connecting internal audit, systematic follow-up, and quality culture to support continuous quality improvement in Islamic elementary schools.